Fraud Using Bank Payment Cards: A Way for Financing of Terrorism and Separatism - Bondaruk, T. G.; Bohrinovtseva, L. M.; Bondaruk, O. S. (Statistics of Ukraine, 2023)
It is substantiated that intensification of terrorism and separatism in Ukraine in time of war rises the priority of problems related with fight against their financing. The banking system, offering a diversity of financial services and tools, is an attractive object for using fraudulent schemes. Money laundering using bank payment cards and with further financing of terrorism and separatism is a significant component of criminal activities. The article’s objective is to explore the main categories of fraud using bank payment cards as a way for financing of terrorism and separatism, and to determine methods for elimination of these activities. The research process involved methods of induction, deduction, system approach, logical generalization, graphic visualization. It was revealed that the fraud was taking new and more sophisticated forms and ways, of which the most common ones were skimming, cash trapping, fishing, or phone call to obtain secret data. It is argued that the principal methods for minimizing the fraud with bank payment cards is raising awareness and financial literacy of bank clients in issues related with various categories of fraudulent actions, as well as modernization and upgrading the software protection system in a bank. It is determined that the current phase of digitalization in the bank sector creates new risks of fraud using bank payment cards for financing of terrorism and separatism. It is substantiated that the system designed to counteract financing of terrorism and separatism by way of fraud involves two mechanisms: identification, by bank employees, of persons applying to banks for financial services, and surveillance of financial transactions made by these persons, to detect the ones that may involve financing terrorism and separatism. The risk zone in Ukraine spreads on the financial transactions that, not being subject to identification, may be used to finance terrorist actions or support separatism. It refers to the financial transactions made by use of payment systems.